Photofusion and Disaggregation of Silver Nanoparticles Suspended in Ethanol by Laser Irradiation - Ortega-Mendoza, Gabriel; Goiz, Oscar; Padilla-Vivanco, Alfonso; Toxqui-Quitl, Carina; Zaca-Moran, Placido; Chavez, Fernando (Current Nanoscience, 2018)
Background: Metal nanoparticles have been widely investigated due to their unique optical, mechanical, and chemical properties compared with those of the same bulk material. These properties can be tuned by controlling their size or shape, in this sense, several nanomaterials have been obtained by means of both chemical and physical methods. For instance, silver nanoparticles have been obtained in liquid media by using laser ablation or chemical reduction techniques. Another way to obtain a colloidal silver nanoparticles is through the well-known pulsed laser irradiation method which can produce a stable colloidal solution in a few minutes of irradiation and without stabilizing molecules or ligands. Methods: Silver nanopowder suspended in ethanol was irradiated with a pulsed laser at 532 nm via optical fiber. Previously, the fiber was prepared by cleaving and removing its coating and then placed in the middle of a cell. The pulse width was 15 ns and the pulse repetition frequency was 10 kHz. Scanning and transmission electron microscopes were used to observe the silver nanoparticles before and after laser irradiation, respectively. The samples were analyzed by means of UV-Vis spectrophotometer to observe the absorption spectra. Results: The absorption spectra show that particle size distribution increases according to the irradiation time. The colloidal solution showed a color change (from gray to yellow) after having irradiated it for 5 minutes. From TEM images, it can be observed that silver nanopowder was transformed to semispherical particles with diameters smaller than 1μm, however, due to the wide particle size distribution the colloidal solution was centrifuged for 30 min to separate the nanoparticles. Conclusion: The pulsed laser irradiation method via optical fiber was successfully used to obtain a stable yellow colloidal solution. Photomelting, photofusion, and photofragmentation are the responsible phenomena for the change in morphology and size of the silver nanopowder.
Keywords: Photomelting